A guide to banking in Britain - Pringle, Robert (London : [New York] : Methuen ; distributed by Harper & Row, Barnes & Noble Import Division, 1975)
Robin Pringle proceeds in this book to give us a detailed, realistic, readable description of how the British banking system works today and of its main developments in the last decade. Criticisms traditionally leveled at the City are examined dispassionately, and the answer to them is given with facts rather than words. From the quantitative and qualitative data that Robin Pringle provides there emerges a clear-cut image of contemporary British banking as an eminently international set-up. A statistic to which he gives due relevance is that of the number of people employed in Britain by foreign banks. And, also quite relevantly, he underlines the close ties which link together, today even more than in the past, the various components of the British financial system.
First appeared in Systèmes bancaires d'Europe occidentale, published in 1970.
Includes bibliographical references and index.
rpm 30/04/2018
Loans
Keywords: Banks and banking; Banks and banking, Foreign; Banking-United Kingdom